Prospective audit of sedation/anesthesia practices for children undergoing computerized tomography in a tertiary care institute - Aakriti Gupta; Indu Sen; Neerja Bhardwaj; Sandhya Yaddanapudi; Preethy J Mathew; Neeru Sahni; Anmol Bhatia (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: The aim of the study was to enumerate the sedative drugs used, assess the efficacy of sedative drugs, and determine the incidence of adverse events. Material and Methods: A prospective audit of children sedated for computerized tomography (CT) by anesthesiology team was conducted for a period of 4 months. The data included patient demographic variables, fasting period, medications administered, adequacy of sedation, imaging characteristics, adverse events, and requirement for escalated care. Results: A total of 331 children were enrolled for sedation by the anesthesia team. The drugs used for sedation were propofol, ketamine, and midazolam. Twenty-two percent children received one sedative drug, 60% children were administered two drugs, and 5% children required a combination of all three drugs for successful sedation. Sedation was effective for successful conduct of CT scan in 95.8% patients without the requirement of a repeat scan. Twelve (5%) children experienced adverse events during the study period. However, none of the adverse events necessitated prolonged postprocedural hospitalization or resulted in permanent neurologic injury or death. Conclusions: The current practice of sedation with propofol, ketamine, and midazolam, either single or in combination was efficacious in a high percentage of patients. The incidence of adverse events during the study period was low.